Comparison of L-Ascorbic Acid Content of Red Dragon Fruit (Hylocereus lemairei (Hook.) Britton & Rose) Based on the Level Maturity - Fitria, Faizatul; Arifah, Farida Noor; Arni, Gerhana Dyeah Gusti; Bashori, Rizka Islamia (Universitas Islam Negeri Alauddin Makassar, 2024)
Introdiction: Red dragon fruit (Hylocereus lemairei (Hook.) Britton & Rose) It has abundant antioxidant content that is able to suppress oxidative stress from free radicals. One of them is vitamin C (L-ascorbic acid is an important molecule in plants and animals that functions as a cofactor of various enzymes. This compound is most abundant in fruits, but the level is affected by the level of ripeness of the fruit. Aims: This study also aims to determine the difference in vitamin C levels of red dragon fruit at different levels of ripeness, namely raw, half-ripe, and ripe.. Result: The analysis used includes qualitative and quantitative using UV-Vis spectrophotometer. The qualitative analysis used three tests, treatment I used FeSO4 5% and NaOH 10%, treatment II with iodine 10%, treatment III used KMnO4 as an oxidizer. All qualitative tests on red dragon fruit from all maturity levels showed positive results with vitamin C content. while quantitative analysis of vitamin C levels showed different levels ranging from raw, half-ripe, and ripe with each value of 0.7112 mg/5g; 0.5380 mg/5g; and 0.3410 mg/5g. Conclusion: These results showed that there was a decrease in vitamin C levels with the increasing level of fruit ripeness